The Developing of Biodiversity Teaching Materials Based on Socio Scientific Issues to Improve Students’ Science Literacy (Journal of Innovative Science Education, 2022)
This study aims to test the feasibility and effectiveness of based biodiversity teaching materials Socio Scientific Issue (SSI) in improving students’ scientific literacy. This research is a Research and Development (R&D) that use the ADDIE model by applying a one group pretest-posttest design. The research subjects to test the teaching materials developed were two expert lecturers consisting of Biology material experts, media experts, practitioners and 125 students of class X MIPA in Kudus. The research instruments are expert validation questionnaire, readability questionnaires of teaching materials and scientific literacy test questions. The analysis of the expert validation questionnaire data showed the average score on the feasibility aspects that were considered very valid. The readability questionnaire analysis describe the teaching materials as having very good readability, which meant that the teaching materials were easy to understand and read by students. The results of the N-Gain analysis of scientific literacy for each aspect of scientific literacy are in the moderate category. The aspect of science as a body of knowledge is 0.49, science as a way of investigation is 0.52, science as a way of thinking is 0.50 and the interaction of science, technology and society is 0.56. Based on the results of the analysis of biodiversity teaching materials based on the Socio Scientific Issue, it is very suitable to be used in learning and is effective in improving students' scientific literacy skills.